China's Growing Engagements with Africa: Challenges and Prospects - Gaurav Pathak; Dr. Santosh Kumar, (Indian Journal of Social Science and Literature (IJSSL), 2025)
This article assesses China's evolving role in Africa, examining whether its influence comes from soft Power, complex power strategies, or a combination of both. As China's demand for resources increases due to its fast-growing economy, the Chinese government has strengthened its engagement in Africa through investments in mining, oil, telecommunications, and infrastructure. These strategies have started a global debate, with critics accusing China of exploiting African resources and imposing neo-colonial debt traps. Employing a dual lens of soft Power and complex strategy, this article investigates China's diplomatic, educational, and humanitarian initiatives alongside its increasing military and economic presence in the region. It assesses China's self-presentation as a peaceful and cooperative partner, in contrast to its geopolitical ambitions, which are reflected in military expansion and resource extraction. By underlining China's multifaceted dominance in cultural exchanges, infrastructure projects, and military operations, this paper examines whether China's presence in Africa promotes genuine development or imposes its economic and strategic control. The findings suggest that China uses soft and hard strategies to secure its interests in Africa while promoting cooperation. Nonetheless, African nations must exercise caution, considering the long-term implications of their interactions with China.